Plankton community of trafficked ports as a baseline reference for Non Indigenous Species arrivals. Case study of the Port of Bar (South Adriatic Sea) - MANDIĆ, MILICA; PESTORIĆ, BRANKA; MARKOVIĆ, OLIVERA; DUROVIĆ, MIRKO; DRAKULOVIĆ, DRAGANA (Mediterranean Marine Science, 2019)
Plankton (ichthyo, zoo and phyto) communities were studied in the temperate shallow waters of the Port of Bar, one of the main cargo ports on the south-eastern Adriatic coast. Sampling was undertaken in February, April, June and October 2015 at 12 stations using the BALMAS Port Baseline Survey protocol. The research was conducted to determine the presence of invasive and potentially toxic plankton species in the port.The most dominant species of ichthyoplankton were eggs and larvae of families Engraulidae, Bothidae and Sparidae with a dominance of Engraulis encrasicolus, Arnoglossus laterna and Diplodus annularis. In addition to ichthyoplankton, sampling of phyto and zooplankton was performed to estimate the abundance and diversity of species. The most numerous zooplankton species throughout investigated period were Penilia avirostris, Euterpina acutifrons, Oithona nana, Acartia clausi, Centropages kroyeri, Paracalanus parvus, Oncaeidae and larvae of Bivalvia. One very unusual occurrence was the spawning of parrotfish Sparisoma cretense (Linnaeus, 1758), a species with Atlantic origin and tropical affinities, whose presence throughout the Mediterranean has shown an increasing trend over the last decade. The most dominant species of phytoplankton were the diatoms Chaetoceros affinis and Chaetoceros spp., Asterionellopsis glacialis, Pseudo-nitzschia spp., Thalassionema nitzschioides, and dinoflagellates Gymnodinium spp. and Prorocentrum triestinum. The potentially toxic species from genus Pseudo- nitzschia reached an abundance of 104 cells L-1. Toxic dinoflagellates Prorocentrum cordatum and P. micans reached values of 103 cells L-1. Although there were no HAOP species found during the survey, presence of several potentially toxic and toxic phytoplankton species whose impact is not sufficiently known indicates the necessity of introduction of regular monitoring activities and definition of preventive protection measures.